1994
DOI: 10.1073/pnas.91.2.594
|View full text |Cite
|
Sign up to set email alerts
|

The B1C8 protein is in the dense assemblies of the nuclear matrix and relocates to the spindle and pericentriolar filaments at mitosis.

Abstract: The B1C8 monoclonal antibody detects a 180-kDa nuclear matrix-specific protein. The protein is a component of the dense, metabolically active bodies or assemblies revealed by resinless section electron microscopy of the nuclear matrix. These assemblies are scattered through the nuclear interior, enmeshed in a complex network of 11-nm filaments. Resinless section electron microscopy of immunogold-stained nuclear matrix preparations shows B1C8 located in many but apparently not all the assemblies. In this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 28 publications
5
49
0
Order By: Relevance
“…By metaphase, UAP56 had moved to the poles of the mitotic spindle and to foci distributed throughout the cytoplasm, but more concentrated around the periphery of the chromosomes. This same distribution is observed for SRm160 at metaphase (Wan et al, 1994), when it might interact with cohesin (McCracken et al, 2005). UAP56 remained at the poles of the mitotic spindle and in smaller cytoplasmic foci through anaphase and into telophase.…”
Section: The Mitotic Choreography Of Uap56mentioning
confidence: 51%
“…By metaphase, UAP56 had moved to the poles of the mitotic spindle and to foci distributed throughout the cytoplasm, but more concentrated around the periphery of the chromosomes. This same distribution is observed for SRm160 at metaphase (Wan et al, 1994), when it might interact with cohesin (McCracken et al, 2005). UAP56 remained at the poles of the mitotic spindle and in smaller cytoplasmic foci through anaphase and into telophase.…”
Section: The Mitotic Choreography Of Uap56mentioning
confidence: 51%
“…SRm160 is a pre-mRNA splicing factor (Blencowe et al, 1998). Like the majority of mRNA splicing factors, SRm160 is not localized at sites of transcription but is instead enriched in nuclear domains called speckles (Wan et al, 1994;Misteli, 2000). When cells are treated with RNA pol II inhibitors, splicing activity is reduced and the speckles become fewer in number, enlarged, and rounded (Misteli et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The antibodies used were: mouse anti-Ran (Transduction Laboratories, Lexington, KY), rabbit anti-Crm1 (from M. Yoshida) (Kudo et al, 1997), mouse anti-nucleophosmin/B23 (from P.K. Chan) (Yung et al, 1985), and mouse (IgM) anti-SRm160 (from J. Nickerson) (Wan et al, 1994). The labeled second antibodies were tetramethylrhodamine B isothiocyanate (TRITC)-labeled donkey anti-mouse or anti-rabbit (Jackson ImmunoResearch Laboratories, West Grove, PA) and Texas Red-labeled goat anti-mouse IgM (Southern Biotechnologies, Birmingham, AL).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Numerous procedures have been used in the isolation of the nuclear matrix and extensive studies by H e et al [25] have shown that low salt extraction gives rise to complete nuclear matrices; 2 M salt extraction after DNase digestion and low-salt treatment of nuclei give rise only to the core filaments of the matrix. Wan et al [36] have more recently stated that high-salt extraction is necessary to obtain the most native nuclear matrix morphology. For our experiments we used three different methods and found that Lyn polypeptides are reproducibly associated with nuclear matrix preparations.…”
Section: Discusslonmentioning
confidence: 99%